THE NEGATIVE IMPACT OF ONLINE SHOPPING SYSTEMS FOR MICRO-ENTREPRENEURS: A PHENOMENOLOGICAL PERSPECTIVE - Alfiqri, Mhd; Hidayatul Insani, Ilmiah; Aulia, Tita; Romadhani, Rizka Andika; Budianto, Lestari; Alamsyah, Lutvi (JPSDa: Jurnal Perbankan Syariah Darussalam, 2024)
This study examines the adverse effects of online shopping systems on micro-entrepreneurs from a phenomenological perspective. As e-commerce platforms expand, micro-entrepreneurs face significant challenges that threaten their survival and growth. Through in-depth interviews and analysis of lived experiences, this research uncovers the multifaceted impact of online shopping systems on these small business owners. Key findings highlight increased competition, reduced profit margins, and the loss of direct customer relationships. Additionally, the study reveals how the technological and logistical demands of e-commerce can overwhelm micro-entrepreneurs who lack the resources and expertise to adapt. The findings suggest that while online shopping systems offer opportunities for broader market access, they also create barriers that can exacerbate existing vulnerabilities within this business segment. By exploring these challenges through a phenomenological lens, this research provides a deeper understanding of the personal and professional struggles micro-entrepreneurs face in the digital marketplace. The study calls for more supportive measures and tailored solutions to help micro-entrepreneurs navigate the complexities of online commerce, ensuring their sustainability and contribution to the economy.